ANALISA PENGUJIAN KUALITAS GAS SF6 PADA PEMUTUS TENAGA (PMT) 66 KV BAY REAKTOR 4R2 DI GITET BANDUNG SELATAN - Dede Siti Nurjannah; Dian Budhi Santoso; Insani Abdi Bangsa (Politeknik Harapan Bersama Tegal, 2021)
Abstract Electrical energy is a necessity that is needed by everyone. To ensure the reliability of electrical energy, the electrical equipment used must be regularly maintained. One of the maintenance carried out is testing the SF6 gas on the power breaker (PMT). This test is carried out to determine the quality of SF6 gas which functions as an insulation medium for PMT. Because when there is a fault current or a normal current at the time the PMT is cut off, an arc will arise which can damage the PMT equipment itself. Therefore, the quality of SF6 gas in PMT must be maintained under normal conditions. In the SF6 gas test, the SF6 Multi Analyzer test tool is used which functions to ensure that the quality of the SF6 gas at PMT is still in good condition. In routine maintenance activities, SF6 gas testing is carried out at 66 kV PMT which is in the 4R2 Reactor Bay. From the test results, the gas purity value of SF6 is 99.9%, the product decomposition or SO2 content of SF6 gas is 26 ppmv, the dew point value is -21.2 ºC, and the pressure value is 0.735 MPa. Based on the test results, there is an anomaly in PMT, namely the results of the SO2 content test in SF6 gas are not normal. The SO2 value exceeds the predetermined standard limit, which exceeds the maximum limit of 12 ppmv. Therefore, in accordance with the analysis of the FMEA method, that is, if there is a bad quality test result for SF6 gas, then SF6 gas replacement and SF6 gas purity testing must be carried out so that there is no widespread disturbance and to ensure the reliability of the electric power distribution system. After replacing SF6 gas, the test results show the value of SO2 = 0 ppmv.